TINJAUAN PERAN HUKUM KEOLAHRAGAAN TERHADAP ATLET PENYANDANG DISABILITAS BERDASARKAN UNDANG-UNDANG NO. 11 TAHUN 2022 - Kusnandar, Belladina Putri Aryani; Farhanah Dita Rahmawati; Rista Aulia Rahma; Putri Madinatul Mukarromah (Law Research Review Quarterly, 2024)
Sport has been recognized as one of the essential activities to fulfill both physical and spiritual needs. In Indonesia, sports have been nationally acknowledged and given special attention by the government. However, there are still challenges in ensuring inclusion and fair rights for people with disabilities in the sports world. This article examines the legal role of sports in relation to athletes with disabilities based on Law No. 11 of 2022. Through a normative juridical approach, the article highlights the rights, coaching, and development of sports for people with disabilities, as well as various government programs to support inclusion and equality in sports. This research supports efforts to create an inclusive and supportive environment for all individuals, including those with special conditions.